Public Expenditure Review : Disaster Response and Rehabilitation in the Philippines - Qian, Rong (World Bank, Washington, DC, 2021)
This public expenditure review (PER) is the first comprehensive assessment of public spending on disaster response, recovery, and reconstruction activities in the Philippines. Despite the high exposure of the country to natural disaster shocks and climate risks, no comprehensive review has been carried out for disaster-related public expenditures. This limited information on disaster expenditure makes it difficult to quantify the total fiscal cost of disasters and evaluate the efficiency of related public spending. This PER was prepared in coordination with the department of budget and management (DBM) as a diagnostic to provide a comprehensive account of post-disaster public spending and to help further improve the flow of funds following disasters and climate-related shocks. Quantifying allocations and identifying challenges in the disbursement of funds following disasters can improve financial preparedness and risk management. A better understanding of post-disaster expenditures helps inform government decisions related to reducing risk and optimizing the allocation of funds. It further helps to: (i) streamline the flow of funds for effective disaster response; (ii) track funds and embedded reallocations; (iii) identify disbursement bottlenecks; (iv) improve oversight of fund utilization; and (v) monitor the achievement of policy targets.